2D metal-organic frameworks with square grid structure: A promising new-generation superlubricating material. (October 2021) - Liu, Lei; Zhang, Yong; Qiao, Yijun; Tan, Shanchao; Feng, Shaofei; Ma, Jing; Liu, Yuhong; Luo, Jianbin
Highlights: A proof-of-concept investigation of 2D MOFs in superlubricity opens up a new road for the market-oriented application. The friction coefficient on MOFs surface can be as low as 5.3 * 10 −4 because of the inorganic-organic hybridization. The plausible friction mechanism for this unconventional material has been identified, namely anchoring effect. By correlating performance with the structure of MOFs, the structure-function relationship was established. Graphical Abstract: ga1 Abstract: It can be inferred from the existing frictional energy dissipation mechanism that metal-organic frameworks (MOFs) may be an ideal material to achieve the solid superlubricity, which is an essential pathway in the energy efficiency. In this work, five MOFs with square grid structure are synthesized, namely Cu(1, 4-BDC)(DMF), Cu(1, 4-NDC)(DMF), Cu(2, 6-NDC)(DMF), Co(1, 4-BDC)(DMF) and Zn(1, 4-BDC)(DMF), and the superlubricity can be achieved on all of these surface (friction coefficient as low as 5.3 * 10 −4 ). Through experiments and DFT simulation, the realization of superlubricity is attributed to two aspects: firstly, the hybrid inorganic-organic structure of MOFs eliminates puckering effect in topographic factors; secondly, the interaction between probe and MOFs is anchoring effect that is so weak as physical adsorption. The anchoring effect is closely related to the structure unit of MOFs that helps us establish the structure-function relationship. When metal nodes and ligands are selected according to the crystal field theory, the friction performance will be optimal for MOFs with the stable coordination. Moreover, the friction performance of MOFs is predictable that gives MOFs great potential in energy conservation.